Degradation of trichloroethylene by toluene dioxygenase in whole-cell studies with Pseudomonas putida F1. - Wackett, L P (1988)
Toluene-induced cells of Pseudomonas putida F1 removed trichloroethylene from growth media at a significantly greater initial rate than the methanotroph Methylosinus trichosporium OB3b. With toluene-induced P. putida F1, the initial degradation rate varied linearly with trichloroethylene concentration over the range of 8 to 80 microM (1.05 to 10.5 ppm). At 80 microM (10.5 ppm) trichloroethylene and 30 degrees C, the initial rate was 1.8 nmol/min per mg of total cell protein, but the rate decreased rapidly with time. A series of mutant strains derived from P. putida F1 that are defective in the todC gene, which encodes the oxygenase component of toluene dioxygenase, failed to degrade trichloroethylene and to oxidize indole to indigo. A spontaneous revertant selected from a todC culture regained simultaneously the abilities to oxidize toluene, to form indigo, and to degrade trichloroethylene. The three isomeric dichloroethylenes were degraded by P. putida F1, but tetrachloroethylene, vinyl chloride, and ethylene were not removed from incubation mixtures.